2020
DOI: 10.1002/mawe.201900099
|View full text |Cite
|
Sign up to set email alerts
|

Study and evaluation of abrasive water jet turning process performance on AA5083

Abstract: In this study, the effect of processing parameters on surface roughness and macro surface characteristics was analyzed during the machining of Ø30 mm and 300 mm aluminum alloy AA5083 abrasive water jets. As the processing parameters (up to 10 mm min−1, 15 mm min−1, 20 mm min−1 and 25 mm min−1), abrasive flow rate (50 g min−1, 150 g min−1, 250 g min−1 and 350 g min−1), the lathe chuck rotational speed (25 min−1, 50 min−1, 75 min−1 and 100 min−1) and the nozzle approach distance (2 mm, 5 mm, 8 mm and 11 mm) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…An approximately threefold increase in the roughness was recorded between v = 5 mm/min and v = 25 mm/min using olivine abrasive grains and a clockwise workpiece rotation direction. A similar trend of Ra variation (Figure 7) with the traverse speed was obtained by Kartal 34 in which Ra increased 16% while increasing traverse speed from 10 to 25 mm/min.…”
Section: Surface Roughnesssupporting
confidence: 80%
See 1 more Smart Citation
“…An approximately threefold increase in the roughness was recorded between v = 5 mm/min and v = 25 mm/min using olivine abrasive grains and a clockwise workpiece rotation direction. A similar trend of Ra variation (Figure 7) with the traverse speed was obtained by Kartal 34 in which Ra increased 16% while increasing traverse speed from 10 to 25 mm/min.…”
Section: Surface Roughnesssupporting
confidence: 80%
“…Grain embedment (Figure 12(e)) on a rotating Ti6Al4V workpiece was also observed by Kartal during disintegration by AWJ. 34 The local shear force induced in the material by the jet, exceeding the ultimate strength of the material (1020 MPa), results in forming a crater (Figure 12(e)) and micro-holes (Figure 12(f)).…”
Section: Surface Morphologymentioning
confidence: 99%
“…In research by Kartal, F., the effects of different processing parameters on the surface roughness and the macro and micro surface characteristics were studied by turning AA5083 aluminum alloy workpiece with different diameters by abrasive water jet. It was concluded that turning speed and abrasive flow rate have the greatest influence on surface roughness; when the lathe chuck rotational speed increases, the nozzle forward speed is low, the abrasive flow rate speed is high, and the nozzle approach distance is low, and a smoother macro surface will be obtained [12]. Ma, Q. et al studied the abrasive recycling of abrasive suspension water jet, and concluded that the recycled abrasive with only large particle impurities being sieved out still has strong cutting ability, and the performance does not decrease significantly after multiple cycles, and the abrasive particle size is controlled at 90 to 180 µM; the quality control of surface roughness is ideal [13].…”
Section: Introductionmentioning
confidence: 99%